STR technique for the detection of contamination by exogenous DNA in paraffin blocks and histological slides - Denise Barcelos; Karina Funabashi; Susana Mazloum; Mariana Fernandes; Leonardo Cardili (BMC, 2019)
Abstract Gastrointestinal Stromal Tumors (GIST) present different types of mutations that may or may not be sensitive to specific target therapy. The laboratory procedure required to prepare histological sections traditionally demands multiple steps, making the process prone to contamination by exogenous genetic material (DNA). An eventual contamination of the biological sample with exogenous DNA may jeopardize subsequent analysis of mutations. The Short Tandem Repeat (STR) technique is frequently used in forensic science fields and presents a potential application in surgical pathology, especially in situations of suspected sample exchange. In the present study, the objective is to verify the possible contamination by exogenous DNA in gastric GIST samples and to evaluate if the presence of contamination can interfere in the detection of the mutations of interest. We assessed eight gastric GISTs by the Sanger sequencing and STR sequence analyses. Seven samples presented more than one profile, a result interpreted as contamination. Our results indicate that exogenous DNA contamination occurred in most of the samples studied and that this was more frequent in samples obtained from the slides than those obtained from the block. The presence of contamination did not inhibit the detection of the mutations of interest for a specific target therapy. Furthermore, the histologic block revealed to be more advantageously when compared to the slide for molecular pathology diagnosis.